(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to examine job rotation and its impact on the empowerment of human resources in commercial banks. The study was conducted at the North Africa Bank, Souk Al-Jumaa Branch. The researcher employed the descriptive analytical approach and used the questionnaire as the main data collection tool, in addition to conducting several interviews with some employees to whom the job rotation method had been applied. The researcher distributed 30 questionnaires using the comprehensive survey method; 25 questionnaires were returned and were valid for statistical analysis. The study concluded that the job rotation approach contributes to a high degree to the empowerment of human resources, despite the presence of some obstacles. The study also recommended the need to motivate and reward human resources according to performance indicators, and to adopt the job rotation approach in order to build trust among human resources working in service institutions by empowering them and granting them sufficient freedom to make decisions and assume responsibility.